Crescimento e caracterização das propriedades físicas do cristal de maleato de L-leucina - OLIVEIRA, Jefferson Santos (2018)
Amino acid crystals have been studied in last years for their tendency to show nonlinear optical properties, which allows their application in frequency converters, photonics and data storage. In this work, L-leucine maleate crystal was synthesized by the slow solvent evaporation method. The material was characterized by the X-ray diffraction (XRD) at room temperature and high temperature (30-100ºC), the crystallographic phase was confirmed by the Rietveld method, with monoclinic crystal system with C2 space group and the following cell parameters a = 21,776 Å b = 5,676 Å, c = 32,125 Å and β = 98,918º. Thermal analysis was performed by Differential Exploration Calorimetry (DSC), Thermogravimetry (TG) and Differential Thermal Analysis (DTA), that shows the material remains stable throughout its solid phase, with only thermal event of fusion around 137ºC about fusion followed by decomposition. We also recorded non-usual thermal coefficients, with a positive α[100] = 148,231x10-6 ºC-1 and two negative ones, α [100] = -5,545x10-6 ºC-1 and α[100] = -4,611x10-6 °C-1. The vibrational study found different modes for the crystal in relation of its formers, and other groups were shifted to smaller or larger wavenumbers.